2005
DOI: 10.3732/ajb.92.6.1033
|View full text |Cite
|
Sign up to set email alerts
|

Species relationships in the genusVasconcellea(Caricaceae) based on molecular and morphological evidence

Abstract: Validity of the taxa currently recognized in the genus Vasconcellea was analyzed by investigating morphological and molecular data from 105 specimens of this genus and six specimens of the related genus Carica. Taxon identification of these specimens was compared with clustering in two phenetic dendrograms generated with 36 morphological characters and 254 amplified fragment length polymorphic (AFLP) markers. Moreover, cytoplasmic haplotypes were assessed using polymerase chain reaction restriction fragment le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 23 publications
4
37
0
12
Order By: Relevance
“…Some studies on papaya have reported intra-and inter-generic analysis using morphological data, isozyme, RFLP (restriction fragment length polymorphism), PCR-based molecular markers like AFLP (amplified fragment length polymorphism), RAPD (random amplified polymorphic DNA), ISSR (inter-simple sequence repeat), DAMD (directed amplification of minisatellite DNA), and microsatellites or SSR (simple sequence repeats) (Jobin-Decor et al, 1997;Parasnis et al, 1997;Van Droogenbroeck et al, 2002;Vitória et al, 2004;Kyndt et al, 2005;Saxena et al, 2005;Ocampo et al, 2006;Silva et al, 2007;Eustice et al, 2008;Oliveira et al, 2010). However, studies that use morpho-agronomic and molecular data together to assess the genetic material used in breeding programs are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on papaya have reported intra-and inter-generic analysis using morphological data, isozyme, RFLP (restriction fragment length polymorphism), PCR-based molecular markers like AFLP (amplified fragment length polymorphism), RAPD (random amplified polymorphic DNA), ISSR (inter-simple sequence repeat), DAMD (directed amplification of minisatellite DNA), and microsatellites or SSR (simple sequence repeats) (Jobin-Decor et al, 1997;Parasnis et al, 1997;Van Droogenbroeck et al, 2002;Vitória et al, 2004;Kyndt et al, 2005;Saxena et al, 2005;Ocampo et al, 2006;Silva et al, 2007;Eustice et al, 2008;Oliveira et al, 2010). However, studies that use morpho-agronomic and molecular data together to assess the genetic material used in breeding programs are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of fats and oils mean the use of lipases as biocatalysts indicates to modify the composition and the distribution in fatty acids of a greasy substance in order to improve the nutritional and/or rheological properties of them. These results have prompted interest in other latex plant extracts, in particular, the unripe fruit of the babaco plant (Kyndt et al, 2005), which contains a latex similar to that in C. papaya. Similarly, babaco (Carica pentagona) has also exhibited biocatalytic activities in lipolysis and acyl transfer reactions (Dhuique-Mayer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Caricaceae family consists of six genera, including Carica and Vasconcellea (Kyndt et al, 2005;Carvhalo and Rennes, 2012). Carica papaya L. is the only species of the genus Carica and the most studied.…”
Section: Introductionmentioning
confidence: 99%